Occlusion and Functional Outcomes after Complete Temporomandibular Joint Resection with Soft Tissue Reconstruction. (21st January 2020) - Lee, Jake J.; Lander, Daniel P.; Jackson, Ryan S.; Zenga, Joseph; Pipkorn, Patrik
Abstract : Reconstructive outcomes after complete temporomandibular joint (TMJ) resection, including the condyle and glenoid fossa bone, are poorly defined in the literature. We described our technique and reviewed occlusion and functional outcomes of 6 consecutive patients undergoing complete TMJ resection and reconstruction with anterolateral thigh free tissue transfer and intermaxillary fixation with elastic bands for 6 to 8 weeks. At median follow‐up of 14 months, median Mandibular Function Impairment Questionnaire score was 32 (range, 4‐38), indicating mild to moderate impairment. Subjective occlusion was normal in 4 of 6 patients. Premature occlusal contact was seen in 2 of 6 patients. Maximal interincisor distance and horizontal mandibular shift with jaw abduction ranged from 29 to 40 mm and 5 to 8 mm, respectively. Four of 6 tolerated regular diets while 2 adhered to mechanical soft diets; no patients were feeding tube dependent. Soft tissue–only reconstruction after complete TMJ resection resulted in good subjective and objective occlusion in 4 of 6 patients and no cases of severe functional impairment.